Significant relationship between the extent of pleural plaques and pulmonary asbestos body concentration in lung cancer patients with occupational asbestos exposure. Issue 4 (11th February 2015) - Yusa, Toshikazu; Hiroshima, Kenzo; Sakai, Fumikazu; Kishimoto, Takumi; Ohnishi, Kazuo; Usami, Ikuji; Morikawa, Tetsuyuki; Wu, Di; Itoi, Kazumi; Okamoto, Kenzo; Shinohara, Yasushi; Kohyama, Norihiko; et al.
Abstract : Background: The aim of this study was to elucidate whether there is a relationship between the extent of pleural plaques and pulmonary asbestos body concentration (PABC). Methods: The subjects were 207 lung cancer patients with occupational asbestos exposure. We determined the plaque extent by findings on chest images using our own criteria. PABCs were measured in resected or autopsy lung specimens. Results: There was a significant relationship between plaque extent and PABC. Seventy‐five percent of the patients determined to have extensive plaques based on our criteria had a PABC of ≥5, 000 asbestos bodies per gram of dry lung tissue, which is one of the certification criteria of lung cancer caused by asbestos for workers' compensation in Japan. Conclusions: In lung cancer patients, the plaque extent had a significant positive relationship with the PABC. The plaque extent would be useful as a proxy for PABC for lung cancer compensation purposes. Am. J. Ind. Med. 58:444–455, 2015. © 2015 Wiley Periodicals, Inc.